Impact produced by seoi-otoshi technique. Relation to years in practice and judo rank - Montero Carretero, Carlos; López Elvira, José Luis (Revista de Artes Marciales Asiáticas, 2014)
Judokas commonly train the seoi-otoshi technique (aka, drop-knee seoi-nage). A controversy exists about the convenience of its use by the younger judokas due to the risk of high loads produced by the impacts on their growing structures. The aim of the present paper was to measure the impacts against the tatami when executing the knee seoi-otoshi technique and its relationship with the years of practice and the degree or level (color of the belt). Thirty-three judokas from different years and degree volunteered to participate. Two force plates covered by standard tatami, registered the ground reaction forces while five consecutive repetitions were executed. We measured the mean and maximum peaks of force relative to their own body weight (BW). The results show peaks of more than 10 BW, which can be considered a potential risk of injury in the younger judokas, especially when repeated in time. In addition, a tendency to decrease the impact as the years of practice increase is observed (potential function; R2= 0.41, p<0.000 in the force peak), and the force in the expert group has been significantly lower than in the other groups (p<0.001). On the other hand, the degree (belt color) shows a quadratic relationship (R2= 0.45, p<0.000 in the force peak). The lack of agreement between the years of practice and the degree shows that the promotion criteria does not appear to be a valid one from a preventive viewpoint, especially in the lower degrees which would correspond to younger practitioners whose locomotor structures are still not fully developed.